1986
DOI: 10.1083/jcb.102.5.1907
|View full text |Cite
|
Sign up to set email alerts
|

The identification of extracellular matrix (ECM) binding sites on the basal surface of embryonic corneal epithelium and the effect of ECM binding on epithelial collagen production.

Abstract: Abstract. Previously, we have shown that embryonic corneal epithelia can interact with, and respond to, soluble extracellular matrices (ECM) (laminin, collagen, and fibronectin). The basal surface of epithelia isolated free of the underlying ECM can be seen to be disrupted by numerous blebs that sprout from this formerly smooth surface. Laminin, collagen, or fibronectin added to the culture medium cause the epithelium to reorganize its cytoskeleton and flatten its basal surface. We show here that ECM molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 29 publications
3
36
0
Order By: Relevance
“…For example, epithelial cells that come in contact with soluble extracellular matrix components acquire characteristics similar to those of mesenchymal fibroblasts, as originally observed by Hay and colleagues (1)(2)(3). After extensive further studies, a concept emerged that the transitional process from epithelial to mesenchymal phenotype is commonly associated with embryonic development, as well as pathological conditions, such as fibrosis or cancer metastasis, and the process was termed ''epithelial-to-mesenchymal transition'' (EMT) (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 80%
“…For example, epithelial cells that come in contact with soluble extracellular matrix components acquire characteristics similar to those of mesenchymal fibroblasts, as originally observed by Hay and colleagues (1)(2)(3). After extensive further studies, a concept emerged that the transitional process from epithelial to mesenchymal phenotype is commonly associated with embryonic development, as well as pathological conditions, such as fibrosis or cancer metastasis, and the process was termed ''epithelial-to-mesenchymal transition'' (EMT) (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 80%
“…Likewise, ECM regulates hepatocyte proliferation and differentiation (18,21). Hay and co-workers have shown that collagen and other ECM components stimulate differentiation and ECM synthesis by corneal epithelium (27,(37)(38)(39)59). In fibroblasts, both messenger translatability and the synthesis of cytoskeletal components require cell-substratum interactions (4,19).…”
mentioning
confidence: 99%
“…By utilizing different culture substrata, matrices have been identified which support differentiated function in a variety of cell types (8,15,16,18) including epithelial cells (2,10,17,20,23). In primary cultures of hepatocytes, albumin synthesis and secretion is maintained for several weeks when cells are plated on a basement membrane-like matrix derived from the Engelbreth-Holm-Swarm mouse sarcoma tumor (EHS gel; described in reference 19) (4).…”
mentioning
confidence: 99%